Sustainable Technologies for Small-Scale Biochar Production—A Review - Kisiki Nsamba, Hussein; Hale, Sarah E.; Cornelissen, Gerard; Bachmann, Robert Thomas (Journal of Sustainable Bioenergy Systems, 2015)
Charcoal has found enormous application in both agriculture (AKA biochar) and other sectors. Despite its potential benefits, small scale technologies relevant for its production remain a chal- lenge. Technologies striking a balance between user friendliness, energy efficiency, ease of adap- tation and limited emissions could easily be integrated into the local community for the sustaina- ble production of biochar answering both technical and socio-economic aspects. These technolo- gies can be customized to recover the produced heat alongside biochar and the producer gas. The purpose of this work is to review the state of the art in small scale technologies, their associated risks and challenges as well as research gaps for future work. Factors affecting biochar production have been discussed and temperature is known to heavily influence the biomass to biochar con- version process. Based on the reviewed work, there is a need to develop and promote sustainable and efficient technologies that can be integrated into biochar production systems. There is also further need to develop portable, economically viable technologies that could be integrated into the biochar production process without compromising the quality of produced biochar. Such tech- nologies at midscale level can be channeled into conventional small scale farmer use in order that the farmers can process their own biochar.
Keywords: Biochar; Technologies; Small Scale; Sustainable; Farmers⁷